Argentina's Trials: New Ways of Writing Memory. (May 2015) - Kaiser, Susana
The last Argentine dictatorship (1976–1983) left a legacy of an estimated 30, 000 desaparecidos (disappeared people). Three decades later, the wall of impunity is now being torn down. Trials are spreading across Argentina and hundreds of repressors are being judged. These trials are public spaces for collective memory making, political arenas for competing memory battles, and forums in which new information and perspectives about what happened under state terrorism continually emerge. Through the testimonies of survivors and the claims of the defense teams we gain new knowledge about the level and scope of the human rights abuses, how the repressive apparatus worked, the everyday "normality" of state terrorism, and society's complicity. La última dictadura argentina (1976–1983) dejó un legado de cerca de 30, 000 desaparecidos. Tres décadas más tarde, el muro de la impunidad está siendo derribado. Los juicios se multiplican por todo el país y cientos de represores están siendo enjuiciados. Estos juicios son espacios públicos para la construcción de la memoria colectiva, escenarios politicos para las batallas sobre la memoria y foros en los que continuamente surgen nuevas perspectivas e información sobre lo ocurrido bajo el terrorismo de estado. A través del testimonio de los sobrevivientes y los reclamos de los equipos de defensa legal surge un nuevo conocimiento acerca del nivel y el alcance de los abusos de los derechos humanos y sobre cómo funcionaba el aparato represivo, la "normalidad" cotidiana del terrrorismo de estado y la complicidad de la sociedad.